2016
DOI: 10.1080/00028487.2015.1114521
|View full text |Cite
|
Sign up to set email alerts
|

Novel Species Interactions in a Highly Modified Estuary: Association of Largemouth Bass with Brazilian Waterweed Egeria densa

Abstract: Frequent invasions in coastal ecosystems result in novel species interactions that have unknown ecological consequences. Largemouth Bass Micropterus salmoides and Brazilian waterweed Egeria densa are introduced species in the Sacramento-San Joaquin River Delta (the Delta) of California, a highly modified estuary. In this system, Brazilian waterweed and Largemouth Bass have seen marked increases in distribution and abundance in recent decades, but their association has not been specifically studied until now. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 58 publications
4
64
0
Order By: Relevance
“…Introduced fishes showed the most consistent increases over time, though the key factors behind the increases likely differ between species. For example, previous studies in the Delta [33] and elsewhere [66,67,68,69] have shown a positive relationship between submerged aquatic macrophytes and fish species within the Centrarchidae family ( e . g .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduced fishes showed the most consistent increases over time, though the key factors behind the increases likely differ between species. For example, previous studies in the Delta [33] and elsewhere [66,67,68,69] have shown a positive relationship between submerged aquatic macrophytes and fish species within the Centrarchidae family ( e . g .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies describing the POD shift in the upper San Francisco Estuary have generally focused on the declining pelagic fish species [16,18,20,29,30,31] that occupy open water habitat and exhibit relatively unique life histories [32]. The few analyses on Delta littoral fish species indicated that major shifts have also occurred in the littoral habitat [24,25,33]. However, such studies are scarce and lack a continuous time series dataset [24] or are more focused on the spatial variation in fish species composition [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Predation on Delta fishes also is affected by ecosystem-level effects of invasives, such as the shift in the food web produced by the non-predatory overbite clam (Corbula amurensis, Cloern and Jassby 2012, Brown et al, forthcoming) or changes in the structural complexity of littoral habitats produced by invasive submerged aquatic macrophytes such as Egeria (Brown et al 2016, forthcoming;Conrad et al 2016). The increase in littoral structural complexity favors invasive species that currently inhabit the Delta, although it may also provide refuge for some prey species.…”
Section: White Crappie Pomoxis Annularismentioning
confidence: 99%
“…These studies have highlighted changes in the fish community (Brown and Michniuk 2007;Grimaldo et al 2012;Conrad et al 2016). This new habitat has also established new food webs (Grimaldo et al 2009b;Young 2016).…”
Section: South-central Deltamentioning
confidence: 99%
“…The invasion and spread of Brazilian waterweed established a new food web. Aquatic macrophytes provide structural complexity and surface area, expanding habitat for epiphytic algae, invertebrates (Schultz and Dibble 2012), and fishes (Brown and Michniuk 2007;Grimaldo et al 2009bGrimaldo et al , 2012Conrad et al 2016).…”
Section: Submerged Aquatic Vegetationmentioning
confidence: 99%